Celebration of London Irish Centre's 1000 mile cycle - London Irish Centre, LIC (1983)
Black and white group portrait photograph of five people holding a large framed photograph of Fr Jim Butler's 1000 mile cycle ride for the London Irish Centre's fundraiser in 1983. The group are (left to right): Mary Kenny, Doris Daly, Fr Jim Butler, Teresa Doyle and Martin Doyle. Photographer unknown.